Haematopoietic alterations in neonates with congenital diaphragmatic hernia receiving extracorporeal membrane oxygenation support. (March 2019) - Dolscheid-Pommerich, Ramona C; Kreuzer, Alexander; Graeff, Ingo; Stoffel-Wagner, Birgit; Mueller, Andreas; Kipfmueller, Florian
Background: Extracorporeal membrane oxygenation procedure (ECMO) has been established in the therapy of respiratory insufficient infants with congenital diaphragmatic hernia. In congenital diaphragmatic hernia newborns, a delay in transfer to an ECMO centre is associated with a sharp increase in mortality. Predictive factors for ECMO support are urgently needed. We evaluated the routine parameters of the first blood withdrawal after birth in congenital diaphragmatic hernia infants, hypothesizing that early signs in bone marrow affecting haematology parameters for early regulation of potentially post birth hypoxia are predictive factors for ECMO support. Materials and methods: In 44 patients born with congenital diaphragmatic hernia, differential blood cell count from the first blood withdrawal after birth was examined. Descriptive statistics included median, 95% confidence intervals, minimum and maximum differentiating ECMO/early mortality vs. no ECMO. Odds ratios with CI were calculated by binary logistic regression analysis. Best predictive markers were further checked in combination with the liver-up situation in two factorial regression models. Results: In our cohort, the survival rate was 77.3% (34/44). While 18 neonates received ECMO support, 26 experienced no ECMO during hospital stay. Odds ratio calculations showed that risk for ECMO support increases with augmenting leukocytes, erythrocytes, haemoglobin, haematocrit, mean cell volume and absolute immature granulocytes. Further, the risk advanced in line with the severity of congenital diaphragmatic hernia assessed by prenatal ultrasound. Conclusions: We conclude that these parameters are associated with disease severity in congenital diaphragmatic hernia newborns and may be considered potentially predictive biomarkers for the necessity of ECMO support.